Homo speculum: reflexos do corpo - Moreira, Júlio Carlos de Oliveira (2018)
Societies can be studied by analyzing various aspects. How individuals organize themselves politically; how they eat; how they treat the environment; how they have sex. I have chosen to analyze what the body of man can say about society. I seek to analyze throughout history, relevant aspects that characterized the importance of the man’s body. A trajectory of facts and opinions that guided the Western world. When one speaks about man’s body, even today, it is a term that is synonymous of the human body. Despite its privileged position in relationship to women for centuries, this modern man lives the extremes of society. It occupies the highest political and economic positions on the globe, but at the same time, also represents the largest contingent of prisoners in jails. The contemporary man is a being who lives social pressures due to the new roles assumed by the woman since the second half of the last century, besides other challenges imposed by the modern life. He tries to locate his position in this new society. A society of performance linked to the logic of consumption as Bauman and Byung-Chul teach us. As a social voyeur I gaze at the body of man to understand the logic that guides our behavior in the second half of the 21st century, where concepts like privacy change with the rising of social networks. A new society of exhibition, where the body becomes a commodity to be worked on to create an intended identity of the individual. And that generates dissatisfaction for those who do not reach the models idealized by that society. But also anxiety among those who have reached valued standards and do not wish to lose them